2020
DOI: 10.3906/sag-2006-375
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related disease: a contemporary review

Abstract: Immunoglobulin G4-related disease (IgG4-RD), is an immune-mediated fibroinflammatory condition, which may involve multiple organs and mostly presents with high serum IgG4 levels and specific histopathological characteristics. As IgG4-RD is a relatively new entity the etiology, prevalence and epidemiologic knowledge is quite limited. Although involvement of almost all anatomical regions has been reported, the most commonly affected regions are pancreas, lacrimal glands, salivary glands, retroperitoneum, orbita,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 94 publications
1
33
0
4
Order By: Relevance
“…Prednisone monotherapy at a dose of 0.6 mg/kg/ day and tapered over the period of 3-6 months is currently considered the first-line therapy. 26 In a recent study, the recurrence rate for IgG4-RD was reported to be 46% after initial treatment with steroids. However, this review of sinonasal disease demonstrated that, of the 14 patients who initially underwent steroid monotherapy, only 1 had recurrent disease (7%).…”
Section: Treatmentmentioning
confidence: 98%
“…Prednisone monotherapy at a dose of 0.6 mg/kg/ day and tapered over the period of 3-6 months is currently considered the first-line therapy. 26 In a recent study, the recurrence rate for IgG4-RD was reported to be 46% after initial treatment with steroids. However, this review of sinonasal disease demonstrated that, of the 14 patients who initially underwent steroid monotherapy, only 1 had recurrent disease (7%).…”
Section: Treatmentmentioning
confidence: 98%
“…Prednisone monotherapy at a dose of 0.6 mg/kg/day and tapered over the period of 3-6 months is currently considered the first-line therapy. 26 In a recent study, the recurrence rate for IgG4-RD was reported to be 46% after initial treatment with steroids. 26 However, this review of sinonasal disease demonstrated that, of the 14 patients who underwent steroid monotherapy initially, only 1 had recurrent disease (7%).…”
Section: Treatmentmentioning
confidence: 98%
“…26 In a recent study, the recurrence rate for IgG4-RD was reported to be 46% after initial treatment with steroids. 26 However, this review of sinonasal disease demonstrated that, of the 14 patients who underwent steroid monotherapy initially, only 1 had recurrent disease (7%). In that case, the addition of rituximab led to clinical improvement.…”
Section: Treatmentmentioning
confidence: 98%
“…Patients can present with subacute development of a mass in the affected organ, even though 60% to 90% of these patients have multiple organ involvement [1]. The prevalence of IgG4-RD is unknown since it is a relatively new entity and still largely underrecognized in clinical practice [2].…”
Section: Introductionmentioning
confidence: 99%
“…The IgG4-RD associated pancreatitis is known as type 1 AIP. IgG4-related endocrinopathies are rare; however, in type 1 AIP, endocrine and exocrine dysfunction develop commonly, manifesting with hyperglycemia and steatorrhea [2]. AIP-related hyperglycemia may be completely controlled after glucocorticoid administration [3].…”
Section: Introductionmentioning
confidence: 99%